From Sībawayhi to ʼAḥmad Ḥasan al-Zayyāt: new angles on the Arabic linguistic tradition - Sheyhatovitch, Beata; Kasher, Almog; Peled, Yishai (Yashi) (Studies in Semitic languages and linguistics, 2020)
Notes on Contributors -- Introduction: Unḥu hād̲ā l-naḥwa... / Beata Sheyhatovitch and Almog Kasher -- In and out of the Metalanguage: Some Reconsiderations of the Technical Vocabulary of Arabic Grammar / Michael G .Carter -- Views Concerning the ʻāmil of the Predicate of the Nominal Sentence Incorrectly Ascribed to Sībawayhi / Aryeh Levin -- Reading Poetry with Sībawayhi: Ittisāʻ/saʻat al-kalām and Metaphorical Thinking in the Kitāb / Avigail Noy -- Aspects of Syntactic Effect (ʻamal) in Arabic Grammatical Tradition:The Term šuġl in Sībawayhi's al-Kitāb and Beyond / Almog Kasher -- Less Familiar Types of ʼan according to Arabic Grammarians / Arik Sadan -- A Sparkle in the Debate about the Word ʼāmīn Used in Supplication and Its Rules in Arabic, by ʼAbū Muḥammad Ibn al-Ḫaššāb (d. 567/1172), an Annotated Translation / Jean N. Druel -- The Theory of Definition in Šarḥ al-Kāfiya by Raḍī l-Dīn al-ʼAstarābād̲ī / Beata Sheyhatovitch -- Comparison to Arabic as an Exegetical Method in Tanḥum ha-Yerushalmi's Commentary on the Bible / Avi Tal -- The Arabic Language Academy in Cairo vis-à-vis a New Grammatical Phrase: The Case of sāfara Muḥammad ʻAlī Ḥasan / Shlomit Shraybom-Shivtiel -- Index.